STUDI PENAMBAHAN SUPEPRPLASTCIZER PADA KUAT TEAN BETON DENGAN VARIASI FAS 0,4 – 0,5 MENGGUNAKAN AGREGAT KASAR YANG DI PECAH (SPLIT) - Muhamad Farhan Kurniawan; Tri Mulyono; Daryati Daryati (Menara: Jurnal Teknik Sipil, 2020)
This study aims to determine the effect of superplasticizer usage on concrete compressive strenght with variation of water cement ratio using subdivided crude aggregates (split). This research cylindrical test object with diameter 15 cm and height 30 cm. Compressive strength concrete design fc’ 35 MPa, with variation of water cement ratio W/C 0,4; 0,45; 0,5 and using Superplasticizer Sikament LN materials 0,5% of the weight of cement and slump value 12 ± 2 cm.The result of research showed an increase the value of concrete compressive strength with the addition of superplasticizer. The average of concrete compressive strength without the addition of superplasticizer and variation of water cement ratio W/C 0,4; 0,45; 0,5 at 28 days in a row is 36,14 MPa, 34,73 MPa, 29,82 MPa. While the value of concrete compressive strength with the addition of superplasticizer increase to 39,73 MPa, 37,18 MPa, 31,23 MPa.